Development of a COVID-19 Vaccination Anxiety Scale to measure COVID-19 vaccine anxiety in Japanese adults - Time Fukuda; Ranno Haruyama; Yuto Tanaka; Shuma Natori; Kohei Koiwa; Koubun Wakashima (PLoS ONE, 2026)
Although COVID-19 vaccines are widely available and effective, vaccination anxiety remains a significant public health challenge that is distinct from behavioral vaccine hesitancy. While various scales measure hesitancy, few specifically capture the multifaceted psychological anxiety regarding COVID-19 vaccines, and none have been validated for the Japanese population. To directly quantify this affective component, this study aimed to develop and validate the COVID-19 Vaccination Anxiety Scale for Japanese adults. A two-wave web-based survey was conducted with 500 Japanese adults. Participants completed the newly culturally adapted 25-item scale alongside validation measures assessing fear of COVID-19, vaccination readiness, conspiracist beliefs, and perceived vulnerability to disease. Test–retest reliability was evaluated after a four-week interval. Factor analyses revealed a three-factor structure: Anxiety Related to Vaccine Confidence, Emotional Symptoms of Anxiety, and Anxiety about Infection after Vaccination. The scale showed good internal consistency and high test–retest reliability, and multigroup analyses suggested approximate comparability of the three-factor structure across gender. Construct validity was supported through significant, theoretically aligned correlations with the external criteria. Specifically, vaccination anxiety was strongly associated with lower vaccination readiness, higher fear of infection, and greater conspiratorial beliefs. These findings highlight that vaccination anxiety is a complex emotional response that requires specific measurement. From a public health perspective, the results suggest that addressing affective concerns—rather than solely providing analytic risk data—is crucial for effective communication. The COVID-19 Vaccination Anxiety Scale provides a useful tool for monitoring population-level anxiety and evaluating targeted interventions in Japan. Future studies should examine whether the same structure is replicated in younger and more age-balanced samples and whether the scale can be adapted for use in other settings.